Pengembangan Aplikasi Pencarian Ayat Terintegrasi dalam Kajian Sains dan Teknologi - Hartono, Nahrun; Baharuddin, Hastuti (Jurnal INSYPRO (Information System and Processing), 2024)
This study explores the key issue of ineffective integration between science and technology studies and religious values at Universitas Islam Negeri (UIN) Alauddin Makassar, with a focus on the Faculty of Science and Technology (FST). Although there have been efforts to integrate these fields, inconsistencies and variations persist, particularly in how Qur’anic verses are used in scientific research. Often, these verses are added superficially without thorough analysis, compounded by students’ challenges in manually finding relevant verses. To address this challenge, the study developed a digital platform aimed at easing the search and integration of religious verses within scientific and technological research. The approach included analyzing user needs, gathering relevant verse data, and testing the platform’s effectiveness and user-friendliness. The findings indicate that the new platform significantly improves the integration of science and technology studies with religious values. Users, including students and researchers, found the platform to be an effective tool for accessing and incorporating Qur’anic verses into their research. As a result, this platform shows promise as a widely adoptable model for fostering a more robust and enduring integration in higher education across Indonesia.